Politeness Strategies Used by Chinese Characters in Movie ‘Everything Everywhere All at Once’ - Rani, Dina Sayyidina; Piyana, Ika; Pratama, Lucky Whyzly; Harpada, Rifky; Amalia, Resti (Berumpun: International Journal of Social, Politics, and Humanities, 2023)
To achieve the communicative aims well, humans need an ability called pragmatic competence, especially for non-native speakers. One of the fields in which pragmatic competence plays a vital role is politeness. Each area has its own rules for politeness regarding the cultural things, including China. Thus, this study aimed to identify the positive politeness strategies used by Chinese characters in the movie entitled Everything Everywhere All At Once. By using descriptive qualitative method, the researchers took the data in the form of utterances said by the Chinese characters in the movie. From 11 data in total, the most used positive politeness strategy is strategy number 4, namely used in group identity markers. The results showed that the use of the positive politeness strategies by the Chinese characters is influenced by their cultural background. Therefore, they still applied it even when they are speaking in second-language. Keywords: Chinese culture, culture, politeness, positive politeness strategy, second-language.